A Note on First-Price Sealed-Bid Cattle Auctions in the Presence of Captive Supplies. (December 2015) - Crespi, John M.; Xia, Tian
Abstract : The authors present an analytical model of a first-price sealed-bid cattle auction in which a spot and coordinated markets are interconnected. The model reveals that the conventional wisdom that market coordination negatively affects the bid price in the spot market is an oversimplification. The relationships between key market variables impact bids and bid shading in complex ways. While captive supplies can lead to lower spot prices, the price reductions do not necessarily stem from an increase in market power due to contracting. The model emphasizes the importance of several variables for future empirical studies.